Macrophage Meets the Circadian Clock: Implication of the Circadian Clock in the Role of Macrophages in Acute Lower Respiratory Tract Infection - Shirato, Ken; Sato, Shogo (Frontiers in Cellular and Infection Microbiology, 2022)
The circadian rhythm is a biological system that creates daily variations of physiology and behavior with a 24-h cycle, which is precisely controlled by the molecular circadian clock. The circadian clock dominates temporal activity of physiological homeostasis at the molecular level, including endocrine secretion, metabolic, immune response, coupled with extrinsic environmental cues (e.g., light/dark cycles) and behavioral cues (e.g., sleep/wake cycles and feeding/fasting cycles). The other side of the clock is that the misaligned circadian rhythm contributes to the onset of a variety of diseases, such as cancer, metabolic diseases, and cardiovascular diseases, the acceleration of aging, and the development of systemic inflammation. The role played by macrophages is a key mediator between circadian disruption and systemic inflammation. At the molecular level, macrophage functions are under the direct control of the circadian clock, and thus the circadian misalignment remodels the phenotype of macrophages toward a ‘killer’ mode. Remarkably, the inflammatory macrophages induce systemic and chronic inflammation, leading to the development of inflammatory diseases and the dampened immune defensive machinery against infectious diseases such as COVID-19. Here, we discuss how the circadian clock regulates macrophage immune functions and provide the potential risk of misaligned circadian rhythms against inflammatory and infectious diseases.